Corruption and Corporate Cash Holdings. Issue 5 (9th April 2022) - Seo, Dong Wook; Han, Seung Hun
ABSTRACT: In this study, we examine the relation between corruption and corporate cash holding policy using data from 35, 288 firms in 44 countries. The results indicate a non-linear relation between corruption and corporate cash holdings with a negative coefficient of the cubic term of corruption. Specifically, in developed (frontier) countries with low (high) level of corruption, we find a negative relation, whereas in emerging countries with moderate level of economic development and corruption, we find a positive relation. Thus, we suggest that corruption is an important variable that affects corporate cash holding policy by the level of economic development.